Citizen Participation in the Digital Era: A Comparative Perspective between Thailand and South Korea - Pornnatcha Wongsa; Grichawat Lowatcharin (Indonesian Association for Public Administration, 2026)
Citizen participation is a vital component of public administration in the 21st century. This study compares Thailand and South Korea to examine how digital governance frameworks influence civic engagement, focusing on policy design, administrative structures, and political culture. The findings reveal that South Korea has effective- ly utilized digital platforms, such as e-participation systems and Open Government Data, to strengthen transparency and enable citizens to engage substantively in au- diting, administrative appeals, and policymaking. In contrast, although Thailand has developed platforms such as the 1111 Complaint System and Damrongtham Online Center, citizen participation remains limited because of structural, legal, and trust barriers. This contrast illustrates that South Korea has reached an advanced stage of digital governance, whereas Thailand is still in its formative phase. Therefore, this study proposes policy recommendations for Thailand, including sustained investment in digital infrastructure, development of integrated platforms, and enhancement of transparency to foster public trust. These measures would expand opportunities for citizen engagement and serve as a pathway to advance public administration toward greater democracy and sustainability.